2016
DOI: 10.1302/2046-3758.57.2000520
|View full text |Cite
|
Sign up to set email alerts
|

WISP3 mutational analysis in Indian patients diagnosed with progressive pseudorheumatoid dysplasia and report of a novel mutation at p.Y198*

Abstract: ObjectivesTo determine the pattern of mutations of the WISP3 gene in clinically identified progressive pseudorheumatoid dysplasia (PPD) in an Indian population.Patients and MethodsA total of 15 patients with clinical features of PPD were enrolled in this study. Genomic DNA was isolated and polymerase chain reaction performed to amplify the WISP3 gene. Screening for mutations was done by conformation-sensitive gel electrophoresis, beginning with the fifth exon and subsequently proceeding to the remaining exons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…In the present study, radiological features consisted of irregular narrow interphalangeal (four patients, Figure 5a), wrist (one patients, Figure 5a), hip (four patients, Figure 5b), knee (three patients, Figure 5c-d), and ankle (one patients, Figure 5e) joint spaces, along with scoliosis and platyspondylia (three patients) (Figure 5g,h). Enlarged metaphysis of the femoral head, short and wide femoral necks, and enlarged tibial metaphysis can be seen in Figure 5b,c Madhuri et al, 2016;Spranger, Albert, Schilling, Bartsocas, & Opitz, 1983;Teebi & Al Awadi, 1986;Temiz et al, 2011;Wynne-Davies et al, 1982). Additionally, the inflammatory parameters of five patients are as follows: normal c-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) levels; negative rheumatoid factor (RF) and autoantibodies such as anti-nuclear antibodies, anti-cyclic citrullinated peptide (CCP) antibody, and anti-citrullinated protein antibodies.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the present study, radiological features consisted of irregular narrow interphalangeal (four patients, Figure 5a), wrist (one patients, Figure 5a), hip (four patients, Figure 5b), knee (three patients, Figure 5c-d), and ankle (one patients, Figure 5e) joint spaces, along with scoliosis and platyspondylia (three patients) (Figure 5g,h). Enlarged metaphysis of the femoral head, short and wide femoral necks, and enlarged tibial metaphysis can be seen in Figure 5b,c Madhuri et al, 2016;Spranger, Albert, Schilling, Bartsocas, & Opitz, 1983;Teebi & Al Awadi, 1986;Temiz et al, 2011;Wynne-Davies et al, 1982). Additionally, the inflammatory parameters of five patients are as follows: normal c-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) levels; negative rheumatoid factor (RF) and autoantibodies such as anti-nuclear antibodies, anti-cyclic citrullinated peptide (CCP) antibody, and anti-citrullinated protein antibodies.…”
Section: Resultsmentioning
confidence: 98%
“…Skeletal changes become increasingly apparent with time and are responsible for the flexion deformities, such as hips and knees. Scoliosis and short trunk can also be observed (Delague et al, 2005;Gao et al, 2013;Luo et al, 2015;Madhuri, Santhanam, Rajagopal, Sugumar, & Balaji, 2016;Sun et al, 2012;Yan et al, 2016;Ye et al, 2012;Zhou et al, 2007). Based on clinical findings, bone X-ray examination should be performed first on suspicion of PPD, and the diagnosis can be confirmed through whole exome sequencing (WES).…”
Section: Introductionmentioning
confidence: 99%
“…This mutation was previously reported in the Human Genome Mutation Database-Public Version (HGMD public) with the code CM991252. The c.210C>A mutation has been reported from several countries, including Italy, France, Lebanon, Syria, Turkey, Germany, India and Iran (6,9,(14)(15)(16)(17)(18)(19). This mutation accounts for almost 28% of the pathogenic variants associated with PPRD.…”
Section: Discussionmentioning
confidence: 99%
“…We reported seven families with SEMD caused by TRPV4 , COL2A1 , CCN6 , SBDS , and ACAN genes in order to explore the relationship between phenotype and genotype of them. Several studies have reported the phenotype–genotype relations of skeletal disorders caused by COL2A1 , COMP , and CCN6 genes ( Barat-Houari et al, 2016a ; Madhuri et al, 2016 ; Liang et al, 2021 ), but we still need more families to prove it, especially Chinese families. Therefore, we summarized the clinical manifestations, radiological data, and molecular features of patients with SEMD, hoping to improve our understanding of Chinese families with SEMD.…”
Section: Introductionmentioning
confidence: 99%